Financial Sector Development and Economic Growth in Developed and Developing Countries from 1970 to 2017 Using Panel Estimation - Saud Ghali Sabr; Younis A. Ahmed; Twana N. Mohamad Khan (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
There is a very important association between the financial sector and economic growth, in order to attaining particular economic goals. More specifically, there are two channels that link the financial sector to economic growth: the Gross Domestic Product (GDP) and the efficiency of resources used by financial intermediaries, who perform the intermediation between the financial sector and those they allocate credit to. Thus, this article explores the long-term nexus between financial development and economic growth in certain developed and developing countries from (1970 – 2017) by using the Johansen panel co-integration test, the panel Dynamic Ordinary Least Squares (DOLS), the panel Fully Modified Ordinary Least Squares (FMOLS) test and the fixed and random effects’ approaches. The empirical results show a significant and positive long-term influence from liquid liabilities and private credit on GDP per capita in developed and developing countries. By contrast, there is a negative correlation coefficient from the deposit money banks' assets and bank deposits on GDP per capita.